Comparative study of the immune responses to the HMS-based fusion protein and capsule-based conjugated molecules as vaccine candidates in a mouse model of Staphylococcus aureus systemic infection. (January 2021) - Ahmadi, Khadijeh; Hasaniazad, Mehdi; Kalani, Mehdi; Faezi, Sobhan; Ahmadi, Nahid; Enayatkhani, Maryam; Mahdavi, Mehdi; Pouladfar, Gholamreza
Abstract: Staphylococcus aureus is a powerful pathogen that causes a wide range of infectious diseases and results in a high mortality rate in humans. Treating S. aureus -related infections is extremely difficult because of its ability to resist many antibiotics; therefore, developing an effective vaccine against this infection can be an alternative and promising approach. In this study, we evaluated the protective effects of a Hla-MntC-SACOL0723 multi-epitope protein (HMS) compared with HMS conjugated to polysaccharides 5 and 8 (CP5 and CP8) of S. aureus and CP5 and CP8 in a mouse sepsis model. To evaluate the type of induced immune response, specific IgG, and antibody isotypes (IgG1 and IgG2a) were determined using the ELISA method. The functional activity of these vaccine candidates was assessed by opsonophagocytosis. Mice were infected with S. aureus COL strain and evaluated for bacterial load in the kidney and spleen homogenates. Th1, Th2, and Th17-related cytokines in the spleen cell supernatants were assessed by flow cytometry. The therapeutic effect of specific anti-HMS protein IgG antibodies against S. aureus COL strain infection was evaluated by passive immunization. HMS recombinant protein induced a higher level of Th1, Th2, and Th17-related cytokines compared with conjugated molecules. Also, mice immunized with the HMS protein reduced the bacterial load in the kidney and spleen more than the one that received the conjugated molecules. Our study suggests that the HMS fusion protein and conjugate molecule vaccine candidates could be suitable candidates for the removal of S. aureus in the mouse sepsis model but HMS protein can be a more effective candidate. Highlights: HMS vaccine candidate increased humoral immune responses and also opsonophagocytic activity. Conjugated vaccine candidate increased levels specific IgG and IgG1 antibodies higher than HMS protein. HMS protein increased Th1, Th2 and Th17 cellular immune responses. HMS protein and conjugated vaccine candidates could decrease the bacterial load in the spleen and kidney of BALB/c mice. The HMS specific polyclonal antibody could decrease the bacterial load in the spleen and kidney of BALB/c mice.